Centroid based person detection using pixelwise prediction of the position - Doležel, Petr; Škrabánek, Pavel; Štursa, Dominik; Zanon, Bruno Baruque; Adrian, Hector Cogollos; Kryda, Pavel (Elsevier Science BV, 2022)
Implementations of person detection in tracking and counting systems tend towards processing of orthogonally captured images on edge computing devices. The ellipse-like shape of heads in orthogonally captured images inspired us to predict head centroids to determine positions of persons in images. We predict the centroids using a fully convolutional network (FCN). We combine the FCN with simple image processing operations to ensure fast inference of the detector. We experiment with the size of the FCN output to further decrease the inference time. We compare the proposed centroid-based detector with bounding box-based detectors on head detection task in terms of the inference time and the detection performance. We propose a performance measure which allows quantitative comparison of the two detection approaches. For the training and evaluation of the detectors, we form original datasets of 8000 annotated images, which are characterized by high variability in terms of lighting conditions, background, image quality, and elevation profile of scenes. We propose an approach which allows simultaneous annotation of the images for both bounding box-based and centroid-based detection. The centroid-based detector shows the best detection performance while keeping edge computing standards.
Detekce osob na základě centroidů pomocí pixelové predikce polohy
Keywords: person detection; fully convolutional networks; performance measure; edge computing; computer vision; detekce osob; plně konvoluční sítě; měření výkonu; edge computing; počítačové vidění